Odpowiedź:
a)[tex]\frac{5x-3}{4}+3=2x/*4[/tex]
[tex]5x-3+12=8x[/tex]
[tex]5x-8x=3-12[/tex]
[tex]-3x=-9/:(-3)[/tex]
[tex]x=3[/tex]
b)[tex]x-\frac{2x+3}{5}=3/*5[/tex]
[tex]5x-(2x+3)=15[/tex]
[tex]5x-2x-3=15[/tex]
[tex]3x=15+3[/tex]
[tex]3x=18/:3[/tex]
[tex]x=6[/tex]
c)[tex]4-\frac{x}{4}=2x-\frac{1}{2}/*4[/tex]
[tex]16-x=8x-2[/tex]
[tex]-x-8x=-2-16[/tex]
[tex]-9x=-18/:-9[/tex]
[tex]x=2[/tex]
d)[tex]\frac{2x}{3}+4=\frac{x+2}{3}/*3[/tex]
[tex]2x+12=x+2[/tex]
[tex]2x-x=2-12[/tex]
[tex]x=-10[/tex]
e)[tex]\frac{3x-2}{5}-2=\frac{x}{5}/*5[/tex]
[tex]3x-2-10=x[/tex]
[tex]3x-x=10+2[/tex]
[tex]2x=12/:2[/tex]
[tex]x=6[/tex]
Szczegółowe wyjaśnienie: